All Days 1999
DOI: 10.4043/10779-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Elastic Modulus Characteristics of Polyester Mooring Ropes

Abstract: One of the most important design factors for FPS mooring systems with polyester ropes is the maximum peak load and excursion during benign-and storm weather conditions. The main rope characteristic which determines the peak load and influences the maximum offset is the dynamic modulus. Several people and institutes (1: Del Vecchio 1998, 2: TTI /NEL JIP 97-98) have made efforts to define the dynamic modulus and to measure relevant data. Del Vecchio was the first attempt to define a formula which covers a lot of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Generally, the methods used to analyze the dynamic responses can be classified into two kinds: quasi-static method [8][9][10][11] and coupled method [12][13][14][15][16][17]. In quasistatic method, flexible riser is modeled as a spring with lumped mass, and only the hydrostatic restoring force exerted upon topend vessel by riser is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the methods used to analyze the dynamic responses can be classified into two kinds: quasi-static method [8][9][10][11] and coupled method [12][13][14][15][16][17]. In quasistatic method, flexible riser is modeled as a spring with lumped mass, and only the hydrostatic restoring force exerted upon topend vessel by riser is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfactory agreement between this formula and the experimental results was also observed by Fernandes et al (1998). The same formula but in a slightly different form was presented by Bosman and Hooker (1999) based on their experimental study.…”
Section: Formula For the Modulus Of A Polyester Ropementioning
confidence: 99%
“…Generally, the analysis methods concerning interactions of top-end vessel and marine structures can be classified into two kinds: the quasi-static method (Ormberg et al, 1997;Kim et al, 2001;Spanos et al, 2005;Wichers et al, 2001;Xu et al, 2009) and the coupled method (Bosman and Hooker, 1999;Chen et al, 2006;Gu et al, 2012;Li et al, 2010;Tahara and Kim, 2003). In the quasi-static method, riser is simplified as a spring with lumped mass.…”
Section: Introductionmentioning
confidence: 99%
“…His results showed that there is a leg vibration mode similar with the platform while the vibration amplitude changes with wave period. Tahara and Kim (2008) employed the empirical formula of the Young's modulus suggested by Bosman and Hooker (1999) to examine the mooring system response of a SPAR undergoing heave. By comparing his result with that of a linearly elastic mooring system, he found a remarkable difference between the two results.…”
Section: Introductionmentioning
confidence: 99%